A Menagerie of Rankings: A Look in RePEc's Factory - Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper provides an overview of RePEc a digital platform for the dissemination of research in economics. Specifically, the focus is on RePEc's main author ranking, which aggregates 36 different rankings based on a range of criteria. The paper first describes the logic behind the ranking and then presents some key descriptive statistics on the top 5% of authors. Notably, the ranking is dominated by English-speaking authors, particularly those affiliated with institutions in the USA. Moreover, less than 9% of authors are female, while around 6% are deceased. Among the living authors, the estimated average age is 60, with over 21% of them aged 70 or above. The paper next discusses the aggregation of the 36 rankings using the harmonic mean, which is RePEc's preferred method. Some counterintuitive properties of this approach are highlighted. Finally, I propose a simpler ranking system based on two criteria –number of journal pages and number of citations– that weight journals and citations according to their qualities and also correct for the number of authors.
Keywords: A14; L11; R32; 330; economists; RePEc; rankings